'Mmm … I love it, bro!': Performances of masculinity in YouTube gaming. (May 2018) - Maloney, Marcus; Roberts, Steven; Caruso, Alexandra
Despite being ubiquitous and embedded in everyday life, 'the centrality of the Internet is still under-theorized in much masculinities research'. Contributing to the knowledge base in this area, here we place under the microscope the performance of hetero-masculinities undertaken by the three most popular YouTube gaming vloggers in 2015–2016: PewDiePie, VanossGaming and Sky Does Minecraft. The focus of this article thus sits at the intersection of YouTube vlogging and gaming cultures, a site that is of particular sociological interest given the latter's associations with the (re)production and function of hegemonic masculinity. In examining the performances and constructions of gender by male gamers on YouTube, our research adds to the growing body of work highlighting the emergence of increasing levels of complexity in the construction of contemporary masculine identities.